Maxizyme-mediated suppression of chikungunya virus replication and transmission in transgenic Aedes aegypti mosquitoes - Mishra, Priya; Balaraman, Velmurugan; Fraser, Malcolm J. (Frontiers in Microbiology, 2023)
Chikungunya virus (CHIKV) is an emerging mosquito borne pathogen of significant public health importance. There are currently, no prophylactic vaccines or therapeutics available to control CHIKV. One approach to arbovirus control that has been proposed is replacement of transmission-competent mosquitoes with those that have a reduced vector capability. Several transgene effectors are being examined as potentially useful for this population replacement approach. We previously demonstrated the successful use of hammerhead ribozymes (hRzs) as an antiviral effector transgene to control CHIKV infection and transmission in Aedes mosquitoes. In this report we examine a maxizyme approach to enhance the catalytic activity and prevent mutants from escaping these ribozymes. We designed a maxizyme containing minimized (monomer) versions of two hRzs we previously demonstrated to be the most effective in CHIKV suppression (Mishra et al., 2016). Three versions of CHIKV maxizyme were designed: Active (Mz), inactive (ΔMz), and a connected CHIKV maxizyme (cMz). The maxizymes with their expression units (Ae-tRNA val promoter and its termination signal) were incorporated into lentivirus vectors with selection and visualization markers. Following transformation, selection, and single-cell sorting of Vero cells, clonal cell populations were infected with CHIKV at 0.05 and 0.5 MOI, and virus suppression was as assessed by using TCID50-IFA, RT-qPCR, and caspase-3 assays. Our results demonstrate that Vero cell clones expressing Mz1 exhibited complete inhibition of CHIKV replication compared to their respective inactive control versions or the two parent hRzs. Five transgenic mosquito lines expressing cMz were generated and transgene integrity was confirmed by splinkerette PCR. Upon oral challenge of transgenic mosquitoes with CHIKV, three out of the five lines were completely refractory to CHIKV infection, and all five lines tested negative for salivary transmission. Altogether, this study 3 demonstrates that maxizymes can provide a higher catalytic activity, and viral suppression as compared to hRzs.